Malignant neoplasms of the vulva: epidemiology and survival of patients in Russia (clinical-population study) - V. M. Merabishvili; I. V. Berlev; A. F. Urmancheeva; E. V. Bakhidze; E. A. Ulrikh (Опухоли женской репродуктивной системы)
Background. Malignant neoplasms of the vulva account for about 4 % of all gynecological cancer neoplasms. Every year in Russia more than 2000 new cases of vulvar cancer are registered, in the North-Western Federal Region of Russia (NWFRR)1 – more than 200 (2022). The incidence rate for Russia as a whole is within 2.5 cases per 100,000 female population (in the NWFRR – about 3,00/0000). Standardized incidence rates for Russia and the NWFRR are within 1.1 and 1.20/0000. Before the age of 30, vulvar cancer practically does not occur; the maximum number (200–300) of cases is registered mainly among women over 60 years of age. There is no information on the mortality rate of the female population for this cancer localization in Russia, as well as calculations of such analytical indicators as mortality and patient survival, information about which can only be obtained on the basis of databases of individual population cancer registries.Aim. To study the prevalence of vulvar cancer based on the newly created population cancer registries database of the NWFRR, to consider the detailed structure of this tumor localization taking into account the fourth digit of the International Classification of Diseases-10, the histological structure of tumors, and the calculation of one-year and five-year patient survival.Materials and methods. The research material is data from the International Agency for Research on Cancer, reference books P.A. Herzen National Medical Research Center of Oncology and National Medical Research Oncology Center, databases of population cancer registries of Saint Petersburg and the NWFRR. Data processing was carried out using licensed programs MS Excel 2013–2016 and Statistica 6.1. To calculate survival, a modified Eurocare program was used, as well as mathematical, bibliographic and statistical methods.Results and conclusion. The first population-based study of the prevalence and effectiveness of anti-cancer measures based on the population cancer registries database, conducted in Russia, showed an increase in morbidity among the female population of malignant tumors of the vulva, decreased mortality of patients at each year of observation. The one-year relative survival rate of patients with vulvar cancer reached 72.0 %, five-year – 41.8 %. One-year survival rate by stage of the disease: I stage – 91.6 %, II stage – 79.7 %, III stage – 53.1 %, IV stage – 29.0 %. Five-year survival rate by stage of the disease: I stage – 68.2 %, II stage – 46.7 %, III stage – 18.6 %, IV stage – 5.6 %.